The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.4049/jimmunol.174.5.2964
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosaLipopolysaccharide Induction of Keratinocyte Proliferation, NF-κB, and Cyclin D1 Is Inhibited by Indomethacin

Abstract: NF-κB is activated during acute inflammatory states as well as in other injury response disease states. Several pathologic states in squamous tissue injury response are characterized by increased squamous proliferation. This study was performed to investigate the hypothesis that Pseudomonas aeruginosa LPS is able to activate a proliferative phenotype in squamous cells via NF-κB induction and that this NF-κB-mediated response may be abrogated with the classic anti-inflammatory agent indomethacin. EMSA, lucifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 63 publications
(59 reference statements)
2
20
0
Order By: Relevance
“…This treatment determined a decrease in the proliferation obtained with CS; thus, the active component involved is at least in part correlated to the presence of lipase. The production of cytokines, angiogenesis, proliferation markers, cell cycle activators and apoptosis resistance are all factors that can contribute to abnormal cellular proliferation (4). We also showed that the CS increased IL-23 production from mononuclear cells in apparent absence of cytotoxicity.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This treatment determined a decrease in the proliferation obtained with CS; thus, the active component involved is at least in part correlated to the presence of lipase. The production of cytokines, angiogenesis, proliferation markers, cell cycle activators and apoptosis resistance are all factors that can contribute to abnormal cellular proliferation (4). We also showed that the CS increased IL-23 production from mononuclear cells in apparent absence of cytotoxicity.…”
Section: Discussionmentioning
confidence: 54%
“…bacterial infection and host inflammatory responses are intimately associated with the development of a full range of abnormal proliferative states in the host tissues that include even the development of cancer (4). The novel pathway of inflammation characterized by the production of Interleukin (IL)-I7 has been described in a variet y of immuneinflammatory diseases (5)(6) .…”
mentioning
confidence: 99%
“…Maspin is a member of the serpin family with well-established anti-metastatic activity in breast and prostate cancers. It was found that the metastatic behavior of isolated cells was dependent on the activation and nuclear accumulation of IKK (Preciado et al, 2005). Repression of Maspin transcription required nuclear translocation of catalytically active IKK , which occur only in advanced prostate tumors that contain inflammatory infiltrates and cells that express receptor activator of nuclear factor kappa-B ligand (RANKL) and LT : (Preciado et al, 2005).…”
Section: Other Tlr-related Moleculesmentioning
confidence: 99%
“…It was found that the metastatic behavior of isolated cells was dependent on the activation and nuclear accumulation of IKK (Preciado et al, 2005). Repression of Maspin transcription required nuclear translocation of catalytically active IKK , which occur only in advanced prostate tumors that contain inflammatory infiltrates and cells that express receptor activator of nuclear factor kappa-B ligand (RANKL) and LT : (Preciado et al, 2005). RANKL can lead to repression of maspin-expression in an IKK -dependent manner (Zou et al, 1994;Luo et al, 2007).…”
Section: Other Tlr-related Moleculesmentioning
confidence: 99%
See 1 more Smart Citation